Détermination Du Seuil De Viabilité De La Position Extérieure Au Maroc: Evaluation Empirique - Fadlallah, Abdellali; Chakhat, Zakaria (European Scientific Journal, ESJ, 2018)
This paper focuses on addressing question on the sustainability of the Moroccan current account. The purpose of this study is to examine theoretical and empirical determinants of the behaviour of the current account deficit in order to apprehend economic policy decisions. An econometric study was conducted in this sense using a vector error-correction model (VECM) during the period (2004Q1-2013Q4). This technique enabled the capture of the longterm relationship. the impact of explanatory variables on the current account was also examined. The examination of the sustainability threshold calculated by the Reisena method revealed that signs of unsustainability have emerged since 2008, which is in line with the results of MFR. However, it is only in 2011 that the current account exhibits deficits that largely exceed the optimal threshold, exposing the national economy to greater vulnerability.